Become an Ummatan Wasathan in Indonesia: Ma'na Cum Maghza Approach to Qs. Al-Baqarah: 143 - Tsalits Nahdliyyatie; HS, Muhammad Alwi; Nurul Hasanah (Al-Wasatiyah: Journal of Religious Moderation, 2023)
The spreading ummatan wasathan concept has always been challenged by the existence of radicalism, terrorism, and intolerance among Indonesian citizens. The topic of ummatan wasathan (QS. Al-Baqarah: 143) was chosen not only as an effort to reduce exclusive actions but also to make it a Muslim character in Indonesia. The problem of this study is how is the contextual understanding of ummatan wasathan as a Muslim character from Ma'na cum Maghza approach? What is the significance of being an ummatan wasathan from Ma'na cum Maghza approach in religion and state in Indonesia? This study uses Ma'na cum Maghza by Sahiron Syamsuddin to uncover the significance of being a ummatan wasathan in Indonesia. This study is library research with a descriptive-analytical method that is reviewed qualitatively. Finally, this study concludes that ma'na and maghza al-tarikhiyah of ummatan wasathan are understood as special or chosen Muslims with the criteria of believing in Allah SWT, being patient and trusting, fair, and upholding unity. Therefore, not all Muslims are ummatan wasathan. As maghza al-mutaharrik of this verse, being an ummatan wasathan signify carried out by Indonesian Muslims, so they can respect each other among citizens and religious communities, and uphold the motto of Bhinneka Tunggal Ika, the foundation of the state, namely Pancasila, and safeguard Negara Kesatuan Republik Indonesia (NKRI).